2016
DOI: 10.1007/s10336-015-1317-z
|View full text |Cite
|
Sign up to set email alerts
|

Excretion patterns of coccidian oocysts and nematode eggs during the reproductive season in Northern Bald Ibis (Geronticus eremita)

Abstract: Individual reproductive success largely depends on the ability to optimize behaviour, immune function and the physiological stress response. We have investigated correlations between behaviour, faecal steroid metabolites, immune parameters, parasite excretion patterns and reproductive output in a critically endangered avian species, the Northern Bald Ibis (Geronticus eremita). In particular, we related haematocrit, heterophil/lymphocyte ratio, excreted immune-reactive corticosterone metabolites and social beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
0
7
1
Order By: Relevance
“…A previous study on northern bald ibis showed that more nematode eggs were excreted in females than in males during the reproductive season [ 26 ], whereas in the present study it was the other way round. Contrary to this previous study, we did not include the egg-laying phase in the data collection, which may be the reason for not finding an elevated excretion of endoparasite products in females.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A previous study on northern bald ibis showed that more nematode eggs were excreted in females than in males during the reproductive season [ 26 ], whereas in the present study it was the other way round. Contrary to this previous study, we did not include the egg-laying phase in the data collection, which may be the reason for not finding an elevated excretion of endoparasite products in females.…”
Section: Discussioncontrasting
confidence: 72%
“…Although individual levels of corticosterone metabolites in parental geese were negatively correlated with the number of offspring [ 19 ], the excretion of nematode eggs increased with family size [ 13 ], indicating that parental effort is costly [ 25 ]. A recent study in northern bald ibis ( Geronticus eremita ) showed that paired individuals excreting high levels of endoparasite products during the reproductive season also engaged in more allopreening behaviour [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, when out of sight the focal ibis was not visible to the observer from the visitor viewing window because the bird was in sheltered areas such as nest boxes, rock crevices or behind trees and bushes. The behavioural ethogram of the study is reported in Table 2 and was prepared basing on preliminary observation of the flock and on previous studies on the Northern bald ibis as well as on relative species ( Hirsch, 1979 ; Kopij, 1998 ; Pegoraro & Föger, 2001 ; Mark, 2007 ; Vargas-Ashby & Pankhurst, 2007 ; Clark et al, 2012 ; Fernández-Juricic, 2012 ; Moulton et al, 2013 ; Frigerio et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Basing on all these indices, a Summary Hygiene Index was created. Following this methodology, after having examined the existing literature, we prepared a list of natural behaviours collected by previous researchers on the NBI as well as on close relative species, in both wild and captive settings ( Hirsch, 1979 ; Kopij, 1998 ; Pegoraro & Föger, 2001 ; Mark, 2007 ; Vargas-Ashby & Pankhurst, 2007 ; Clark et al, 2012 ; Fernández-Juricic, 2012 ; Moulton et al, 2013 ; Frigerio et al, 2016 ). The list included 18 items that were grouped in four subsets basing on the behavioural function ( Table 3 ) ( Kopij, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…The altruistic behaviour, allopreening is widespread amongst birds, especially in aggregating species (Waltman and Beissinger 1992;Radford and Du Plessis 2006;Cox 2012;Gill 2012). One obvious benefit is the removal of ectoparasites and maintenance of plumage condition, although close proximity may also aid the transmission of parasites (Frigerio et al 2016). Allopreening also appears to have important social functions, with some studies suggesting it promotes pair bonding (Barbour and Degange 1982), buffers the negative effects of social stress (Scheiber et al 2005;Hennessy et al 2006;Stoẅe et al 2008) and reduces the likelihood of interspecific conflicts and associated breeding failures (Lewis et al 2007).…”
Section: Introductionmentioning
confidence: 99%